2019
DOI: 10.1371/journal.pone.0226151
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses of wheat seedlings to osmotic stress induced by various osmolytes under iso-osmotic conditions

Abstract: Many environmental stresses cause osmotic stress which induces several metabolic changes in plants. These changes often vary depending on the genotype, type and intensity of stress or the environmental conditions. In the current experiments, metabolic responses of wheat to osmotic stress induced by different kinds of osmolytes were studied under iso-osmotic stress conditions. A single wheat genotypes was treated with PEG-6000, mannitol, sorbitol or NaCl at such concentrations which reduce the osmotic potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 34 publications
2
55
0
6
Order By: Relevance
“…6 ). Starch hydrolysis, galactose or raffinose accumulation have also been detected previously in wheat under drought and different osmotic stress conditions 47 , 48 . In this experiment, an unidentified sugar compound ( S1 ) was also separated between the maltose and raffinose.…”
Section: Resultssupporting
confidence: 71%
“…6 ). Starch hydrolysis, galactose or raffinose accumulation have also been detected previously in wheat under drought and different osmotic stress conditions 47 , 48 . In this experiment, an unidentified sugar compound ( S1 ) was also separated between the maltose and raffinose.…”
Section: Resultssupporting
confidence: 71%
“… 55 Sugars, such as GABA, galactose, fructose, and mannose, serve as metabolic precursors in many metabolic processes in plants. 56 In addition, starch, sucrose, and galactose metabolism was altered in Jatropha curcas drought-treated plants. 57 Also, pathways such as sucrose and starch metabolism and pentose and glucuronate interconversion were induced at the fiber initiation stage of cotton under drought stress, suggesting the regulation of sugar and energy metabolism to adapt to drought stress.…”
Section: Resultsmentioning
confidence: 99%
“…Nxele et al [8] observed a similar level of MDA in stressed plant under salinity and drought, but salinity stimulated more proline content. Recent study on wheat seedling also reported that NaCl stress stimulated proline accumulation dramatically, PEG induced accumulation of sugar metabolites (glucose, fructose) and glycine betaine, while polyamines' synthetic pathway was also altered by various osmolytes [26]. Furthermore, under salt stress, turgor would be maintained by transporters such as Na + /H + antiporter, H + -pyrophosphatase, high efficiency potassium transport [5], and aquaporin, which is specific transporter for water [6].…”
Section: Discussionmentioning
confidence: 97%
“…This should be attributed to roots having a higher ability to adapt to osmotic stress [23]; therefore, root growth rate can be stably maintained under various levels of PEG-induced osmotic stress [54]. Moreover, recent study revealed that the biosynthetic pathway of polyamines, including spermine, spermidine and putrescine, which participate in cell division and differentiation [55], also mediated under osmotic stress, and PEG leaded to increase of spermine, spermidine and putrescine [26].…”
Section: Discussionmentioning
confidence: 99%